Halal Orientation Strategy To The Company's Financial Performance: A Study on the Halal Industry Considering Indonesian Culture - Bawono, Anton; Pratama, Abdul Aziz Nugraha (Faculty of Islamic Economics and Business Sultan Aji Muhammad Idris State Islamic University Samarinda, 2024)
This study examines the influence of the halal orientation strategy on the financial performance of companies, especially MSMEs based on the halal culture in Indonesia as a direct variable and a moderating variable. MSMEs were chosen as the research object due to their large proportions in Indonesia. This study is a quantitative research using primary data collected through a survey. The survey was carried out on MSME owners in Joglosemar (Jogja, Solo, and Semarang) and the surrounding areas. The data was processed using SEM (Structural Equation Model) PLS (Partial Least Square) to find out the relationship between the variables used in the model. Based on the test results, halal culture has a positive and significant relationship to financial performance as a direct variable, but it has no relationship as a moderating variable. Another variable that shows a positive and significant relationship is employee engagement. This is one of the first studies examining the relationship between halal orientation strategies and company financial performance. The findings can encourage MSMEs to implement a halal orientation strategy as part of improving the company's financial performance by establishing a halal culture and increasing employee engagement. It is also one of the first studies in Indonesia that examine the halal orientation strategy with a focus on MSMEs comprehensively.